Short-Term Periodic Fasting Reduces Ischemia-Induced Necrosis in Musculocutaneous Flap Tissue - Andrea Weinzierl; Maximilian Coerper; Yves Harder; Michael D. Menger; Matthias W. Laschke (Biomedicines, 2024)
Periodic fasting (PF) as a form of dietary restriction has been shown to induce tissue-protective effects against ischemic injury in several different tissues. Accordingly, in this study we analyzed whether a short-term 24 h fast is suitable to prevent necrosis of musculocutaneous flap tissue undergoing acute persistent ischemia. C57BL/6N mice were randomly divided into a PF group (n = 8) and a control group that was given unrestricted access to standard chow (n = 8). The PF animals underwent a 24 h fast immediately before flap elevation and had unrestricted access to food for the rest of the 10 day observation period. Musculocutaneous flaps with a random pattern design were dissected on the animals’ backs and mounted into dorsal skinfold chambers. On days 1, 3, 5, 7 and 10 after surgery, nutritive tissue perfusion, angiogenesis and flap necrosis were evaluated using intravital fluorescence microscopy. Thereafter, the flap tissue was excised and fixed for histological and immunohistochemical analyses. The flaps of PF-treated animals exhibited a higher functional capillary density and more newly formed microvessels, resulting in a significantly increased flap survival rate. Moreover, they contained a lower number of myeloperoxidase (MPO)-positive neutrophilic granulocytes and cleaved caspase-3-positive apoptotic cells in the transition zone between vital and necrotic flap tissue. These findings indicate that short-term PF improves tissue survival in ischemically challenged musculocutaneous flaps by maintaining nutritive blood perfusion and dampening ischemia-induced inflammation.